Short Synthesis of a Biphenyl-Based Amino Triflamide Catalyst and Its Application in Enamine Catalysis - Uwaso, Yuki; Yokoyama, Naoki; Kano, Taichi (Synlett, 2023)
A novel axially chiral biphenyl-based amino triflamide has been designed and successfully synthesized from 1-nitropyrene in 6 steps. This chiral amino triflamide functions as effective catalyst for asymmetric Mannich reaction through enamine intermediates.
Keywords: axial chirality; biphenyl; amine organocatalyst; enamine catalysis; Mannich reaction; aminoxylation